The Role of SAMOTA Tourism Development in Enhancing the Revenue of Micro, Small, and Medium Enterprises Customers in the Region of Big Sumbawa - M. Nur Febriansyah; Amirul Mustofa; Sri Roekminiati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research examines the growth of SAMOTA tourism and the increase in income of small and medium enterprises (MSMEs). The author of this study used a qualitative descriptive data analysis method primarily to collect information about the tourist attractions used as research locations. Qualitative research is based on interpretive philosophy or postpositivism and is used to conduct research in natural conditions, where the researcher acts as the primary tool. The data is usually qualitative because it combines observation, interviews, and triangulated documentation. Data is analyzed inductively or qualitatively, and the results are the result of research. The research results show that tourism in the Samota region is experiencing development. The area on Sumbawa Island called SAMOTA has been designated a Biosphere Reserve by the UN and UNESCO. The tourism development process increases the number of visitors to the SAMOTA tourist area. That can increase income and encourage people to build new MSMEs to meet increasing visitor demand. Developments in the SAMOTA tourist area have tremendously impacted the MSME sector. Samota's tourism development helps make more money. MSME players are happy with the many events in Sumbawa because they benefit from them